Cardiac biomarkers of disordered eating as a function of diagnostic subtypes. (December 2020) - Green, M.A.; Miles, L.; Sage, E.; Smith, J.; Carlson, G.; Hogan, K.; Bogucki, J.; Ferenzi, L.; Hartman, E.; Tao, Y.; Peng, Y.; Roche, A.I.; et al.
Abstract: Objective: The purpose of this study was to identify cardiac biomarkers of disordered eating as a function of diagnostic subtype as assessed via self-report inventory. Method: Mean heart rate (HR), systolic and diastolic blood pressure, mean R wave amplitude (mV), mean T wave amplitude (mV), QTc interval ( sec ), Tpeak-Tend interval prolongation (sec), QTc interval prolongation (sec), QRS prolongation (sec), and spectral indicators of cardiac dysfunction (LF/HF spectral ratio, HF spectral power) were assessed via electrocardiography among women with no eating disorder symptoms ( n = 32), subclinical eating disorder symptoms ( n = 92), anorexia nervosa ( n = 7), bulimia nervosa ( n = 89), binge eating disorder (BED: n = 20), and other specified feeding and eating disorders (OSFED: n = 19). Results: MANOVA results showed statistically significant group differences. Follow-up tests revealed significantly decreased mean R wave amplitude among participants with self-indicated clinical (bulimia nervosa, binge eating disorder) and subclinical forms of disordered eating compared to asymptomatic controls. Discussion: Results suggest decreased mean R wave amplitude is a promising cardiac biomarker of disordered eating. Highlights: Cardiac biomarkers are promising indicators of eating disorder symptom status. Decreased mean R wave amplitude is a sensitive cardiac biomarker. Decreased mean R wave amplitude may be a useful indicator of eating disorder symptom status.